TREATMENT OF ORBITAL FRACTURES: SURGICAL AND CONSERVATIVE APPROACHES (International Seven Journal of Multidisciplinary, 2025)
Orbital fractures are common and complex facial trauma injuries, with the potential to cause significant functional and aesthetic impairments such as diplopia and enophthalmos. Proper management depends on accurate diagnosis, often supported by Computed Tomography (CT), to identify emergencies such as Orbital Compartment Syndrome and muscle entrapment in “trapdoor” fractures. Most cases allow for an initial conservative approach. However, surgery is indicated in the presence of persistent diplopia, significant enophthalmos, or large bony defects. Surgical techniques have evolved to include materials such as titanium meshes and personalized implants, although complications and the need for reintervention remain challenges, especially due to improper implant positioning.